2020
DOI: 10.1186/s12974-020-02042-6
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid ameliorates intestinal alterations associated with EAE

Abstract: Background Multiple sclerosis (MS) is a chronic demyelinating autoimmune disease affecting the CNS. Recent studies have indicated that intestinal alterations play key pathogenic roles in the development of autoimmune diseases, including MS. The triterpene oleanolic acid (OA), due to its anti-inflammatory properties, has shown to beneficially influence the severity of the experimental autoimmune encephalomyelitis (EAE), a preclinical model of MS. We herein investigate EAE-associated gut intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 61 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Anyway, it is generally accepted that OA and related triterpenoids exhibit a very moderate aptitude as radical scavengers [ 158 ]. Still, Gutierrez et al [ 159 ] found that treatment with OA prevented lipid peroxidation and superoxide anion accumulation in the gut, while inducing the expression of the ROS scavenger Sestrin-3, which was associated with a normalization of the levels of intestinal mucosal dysfunction markers, as well as the pro- and anti-inflammatory immune bias in a murine model of experimental autoimmune encephalomyelitis.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Anyway, it is generally accepted that OA and related triterpenoids exhibit a very moderate aptitude as radical scavengers [ 158 ]. Still, Gutierrez et al [ 159 ] found that treatment with OA prevented lipid peroxidation and superoxide anion accumulation in the gut, while inducing the expression of the ROS scavenger Sestrin-3, which was associated with a normalization of the levels of intestinal mucosal dysfunction markers, as well as the pro- and anti-inflammatory immune bias in a murine model of experimental autoimmune encephalomyelitis.…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…Although many mechanisms have been proposed to underlie their effects, a unifying proposal is that oxidative stress and inflammation represent a common pathway of injury. In this review, we have presented evidence indicating that OA plays an efficient role in preventing lipid peroxidation and superoxide anion accumulation [ 159 ] and reinforces the endogenous intracellular antioxidant. On the other hand, investigations in cell cultures and experimental animals have demonstrated that OA significantly inhibits pro-inflammatory cytokine production (IL-1β, IL-6, IL-8, TNF-α, MCP-1) in a number of inflammation and oxidative stress scenarios [ 102 , 189 , 190 ].…”
Section: A Unifying Hypothesis Of the Oleanolic Acid Pharmacological ...mentioning
confidence: 99%
“…Altogether these studies clearly demonstrate the importance of the microbiota composition in determining the inflammatory environment in the gut, and its consequences on the CNS. It is highly relevant to MS that dysbiosis in patients is frequently associated with an increased intestinal permeability (84) and both alterations have been also demonstrated in EAE (85)(86)(87). That such conditions might promote a systemic inflammatory condition is supported by the increased plasma levels of LPS observed in both MS patients and EAE-affected mice (88,89), as well as by the increased anti-microbiota systemic IgG responses observed in MS patients, which suggest an enhanced bacterial translocation from the gut lumen to systemic circulation in MS (90).…”
Section: Gut-brain Cross-talkmentioning
confidence: 99%
“…[32] Anti SARS-CoV-2 (COVID-19) [33,34] normalise the levels of gut mucosal dysfunction markers, reshape the gut microbiota [35], treatment of human Multiple schlerosis [36], Suppress liver carcinogenesis [37] Improves obesity-related inflammation and insulin resistance [38] Antidiabetic [39], α-glucosidase inhibitor [40], protect skin aging [41] Peripheral anti-nociceptive and anti-inflammation effect…”
Section: Nobilin D Ethanol/bibenzyl Derivativesmentioning
confidence: 99%